A NEW SPECIES OF THE GENUS Macrinus SIMON, 1887 (ARACHNIDA: ARANEAE: SPARASSIDAE) FROM NORTHERN BRAZIL (Boletín de la Sociedad Zoológica del Uruguay, 2025)
The genus Macrinus Simon currently includes six species occurring mostly in South America, with records from the island of Tobago, Venezuela, Guyana, Ecuador, Bolivia and Brazil. A single species is found in the Mohave desert in California, USA. In this paper, I describe a new species of Macrinus based on a single female from the state of Pará, northern Brazil. The new species can be easily distinguished from its congeners by the shape of the median septum in the epigyne resembling a chess pawn. In addition, I provide new records for M. succineus Simon, M. pollexensis (Schenkel) and M. jaegeri Rheims and an updated distribution map for all South American species.
Keywords: Macrinus aisenbergae spec. nov.; Neotropical region; new records; taxonomy